Effect of Dietary Nori (Dried Laver) on Blood Pressure in Young Japanese Children: An Intervention Study - Keiko Wada; Michiko Tsuji; Kozue Nakamura; Shino Oba; Sakiko Nishizawa; Keiko Yamamoto; Kaori Watanabe; Kyoko Ando; Chisato Nagata (Journal of Epidemiology, 2021)
Background: Few studies have examined the association between seaweed intake and blood pressure in children. We conducted an intervention study to investigate whether seaweed intake affects blood pressure. Methods: Subjects were children aged 4 to 5 years attending a preschool in Aichi Prefecture, Japan, in 2010. Among 99 students, 89 (89.9%) were enrolled in our study. Nori (dried laver), an edible seaweed widely consumed in Japan, was used as a dietary intervention. Children in the intervention group were asked to consume 1.76 grams per day of roasted nori in addition to standard meals for 10 weeks. Children in the control group consumed their usual diet. Before the intervention and at the 10th week of the intervention, children’s blood pressure was measured three times successively using an automated sphygmomanometer with subjects in a sitting position. Changes in systolic (SBP) and diastolic blood pressure (DBP) were compared between 55 children in the intervention group and 26 in the control group after adjustment for SBP and DBP before the intervention. Results: Changes in SBP were −8.29 mm Hg in the intervention group and +0.50 mm Hg in the control group (P for difference in change = 0.051). Changes in DBP were −6.77 mm Hg in the intervention group and −0.05 mm Hg in the control group (P = 0.031). In girls, no difference in blood pressure changes was found between the intervention and control groups. Conclusion: Nori intake lowered DBP level in boys. Seaweed intake might have preventive effects on elevated blood pressure in childhood.